An Analysis of Students’ Intrinsic Learning Motives in Studying Grammar at the English Department of Bung Hatta University - Merry Prima Dewi (Politeknik Negeri Padang, 2017)
This research aimed to find out English Department students’ intrinsic learning motive in studying Grammar. Students could not apply correct Grammar in speaking and writing, many students repeated grammar subject, and remedial teaching was conducted. Those problems indicate that students have problems concerning about their motive in studying Grammar. This research is a composite of quantitative and qualitative research by using explanatory sequential design”. The participants of the research were all students of FKIP, Bung Hatta Univeristy. The instruments to collect the data were questionnaire, interview, and observation. The technique of data analysis was initiated by calculating the mean of each questionnaire items as the quantitative data. Qualitative data analysis wasgained from the result of the interview and observation. The result gained from the quantitative and qualitative data analysis was interpreted, and research finding was gained. The finding of the research shows that the tendency of students’ intrinsic learning motives are for utilizing Grammar knowledge in order to get a good job and gaining score compared to the motives of gaining Grammar knowledge and developing Grammar knowledge